Chronology and geochemistry of Late Carboniferous volcanics in Bogda, Xinjiang: implications for the tectonic evolution of the Eastern Tianshan - Wang, Wen-Jia; He, Yu-Li; Xu, Lei; Xu, Wen-Bo; Ren, Wen-Xiu; Wang, Huai-Tao (Frontiers in Earth Science, 2023)
The Late Carboniferous volcanic magmatic evolution in the Bogda Orogenic Belt is considerably important for understanding the evolution history of the Eastern Tianshan in the Central Asian Orogenic Belt. Our study focuses on the Upper Carboniferous Liushugou Formation in the Liudaogou and Qidaogou sections of Xishan Township in eastern Bogda. By analyzing the volcanics and sedimentary sequences, we present paleontological evidence, new zircon U–Pb ages, and geochemical data of the volcanics. The lithological composition of volcanics ranges from basic to acidic. The rhyolite has an age of 311.2 ± 1.7 Ma, which, when combined with guide fossils Plerophyllum sp., Zaphrentoides sp., and Zaphrentites sp., indicates its formation in the Late Carboniferous. The geochemical and zircon Lu–Hf isotopic data (εHf(t) = 8.0–11.9) indicate that the basalts originated from a metasomatized subcontinental lithospheric mantle, while andesites and rhyolites were products of crystallization differentiation of the basalts that underwent assimilative mixing. Based on the published data, we propose that the tectonic evolution, transitioning from island arc magmatic systems to post-collisional orogenic belts, commenced in the Bogda Orogenic Belt toward the end of the Late Carboniferous.